Effectiveness of Composter with Magic Compos System Forward Reverse Design Through Temperature and Humidity Control on Composing Quality - Amaliyah, Nurul; Anwar, Taufik; Wardoyo, Slamet (Poltekkes Kemenkes Palu, 2023)
Household waste management is an important concern in an effort to reduce the potential negative impact on public health due to organic waste generation. This study aims to analyze differences in compost maturation rates based on variations in the time interval of the turning process in Magic Compost, differences in compost maturation rates based on the type of organic waste, differences in C/N ratio, carbon content, and moisture content in compost, differences in nitrogen, phosphorus, and potassium levels in compost, and differences in temperature, pH, and color in compost based on household organic waste criteria. This research uses an experimental approach with a posttest without a control group design and applies a randomized complete group design (RAKL). The tool used is Magic Compost, which is equipped with a temperature and humidity controller. The results showed a significant difference in the rate of compost maturation based on the time interval variation of the turning process on Magic Compost (p value = 0.000). The best turning time interval is 12 hours. There was a difference in the rate of compost maturation based on the type of organic waste generated by households, with mixed waste compost maturing the fastest and rice/starch waste maturing the slowest (p value = 0.001). While there was no difference in the C/N ratio (p value = 0.202), there were significant differences in the carbon content and moisture content of the compost based on the type of organic waste (p values = 0.042 and 0.000). However, there was no difference in the nitrogen and phosphorus content of the compost (p value = 0.144 and p value = 0.663). There was a difference in potassium levels in the compost based on the type of organic waste (p value = 0.000). The temperature of the resulting compost showed no significant difference (p value = 0.000), but there were differences in the pH and color of the compost based on household organic waste criteria (p values = 0.048 and 0.007). This study provides important insights into organic waste management through composting with Magic Compost, which can be an effective solution for reducing the negative public health and environmental impacts caused by organic waste generation.